1989
DOI: 10.1055/s-0038-1646882
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Reduce the Risk of Cardiovascular Events in Subjects Suffering from Intermittent Claudication of the Lower Limbs?

Abstract: SummaryThis study meta-analysed randomized, double-blind, placebo controlled trials in patients with intermittent claudication of the lower limbs comparing ticlopidine to placebo in order to test the hypothesis that the drug, a pure antiplatelet agent, is able to reduce the incidence of thrombotic cardio-vascular events on atherosclerotic arteries in these patients. A highly significant reduction, from 9% to 3% (p ranging from 0.006 to 0.002), was observed for fatal or non-fatal cardio-vascular events in a tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The total mortality was 26.1% in the placebo group and 18.5% in the treated group, a significant reduction of about one third, mostly due to a marked decrease (-44% ) of cases of fatal ischaemic heart disease. Similar results had been anticipated by the pooled analysis [27] conducted on several Ticlopidine studies: total cardiovascular events appe ared to be reduced by on third (3.0% versus 9.0%) in the Ticlopidine pooled groups versus the placebo groups.…”
Section: B3 Effect Of Antithrom Botic Drugs On Cardiovascular Eventssupporting
confidence: 73%
See 1 more Smart Citation
“…The total mortality was 26.1% in the placebo group and 18.5% in the treated group, a significant reduction of about one third, mostly due to a marked decrease (-44% ) of cases of fatal ischaemic heart disease. Similar results had been anticipated by the pooled analysis [27] conducted on several Ticlopidine studies: total cardiovascular events appe ared to be reduced by on third (3.0% versus 9.0%) in the Ticlopidine pooled groups versus the placebo groups.…”
Section: B3 Effect Of Antithrom Botic Drugs On Cardiovascular Eventssupporting
confidence: 73%
“…A re-appraisal of the data of the Physician's Health study indicated that chronic admi nistration of low dose aspirin (325 mg on alternate days) given for 5 years in a double blind fashion to a large population of physi cians, was associated with a significantly lowered (around 50%) incidence of perip heral arterial surgery in comparison with placebo [26], The reduction was even greater in those subjects who had intermittent clau dication at baseline. Also in an overview of several studies of claudicant patients treated with Ticlopidine the need of amputation or vascular surgery was reduced from 8 to 2.8 per hundred patient/years [27]. Finally, in the PACK study [28], the rate of amputation was almost halved in the Ketanserin versus the placebo group.…”
Section: B) Intermittent Claudicationmentioning
confidence: 99%
“…25 In addition, the Swedish Ticlopidine Multicentre Study randomized 687 claudication patients to treatment with ticlopidine or matching placebo and demonstrated a lower mortality from ischemic heart disease in the ticlopidine group. 26 In addition, a recent, large, unblinded, Italian trial documented a 46.3% reduction in risk of vascular death or nonfatal myocardial infarction in unstable angina patients treated with ticlopidine (/J=0.009).…”
Section: Cardiovascular Eventsmentioning
confidence: 99%
“…[7][8][9][10][11] Therapy with ticlopidine, an inhibitor of platelet aggregation, increases the distance that patients are able to walk 12 ; reduces the rate of death, myocardial infarction, and stroke; and reduces the need for reconstructive arterial surgery of the leg in patients with intermittent claudication. [13][14][15][16] Moreover, as compared with placebo, ticlopidine increases the immediate and one-year patency of aortocoronary bypass grafts. 17,18 We undertook the present study to determine whether ticlopidine could reduce the rate of late occlusion of saphenous-vein grafts below the knee.…”
Section: Discussionmentioning
confidence: 99%